Population structure and genetic stock identification in southeastern United States loggerhead sea turtles (Caretta caretta) using genome-wide SNPs - Ian Silver-Gorges; Lisa M. Komoroske; Jamie Adkins; John D. Swenson; David S. Addison; Derek A. Burkholder; Dean A. Bagley; Glenn D. Goodwin; Kristen M. Hart; Joseph B. Pfaller; Brian M. Shamblin; Mariana M. P. B. Fuentes (Conservation Genetics, 2026)
Characterizing the genetic structure and connectivity between populations of endangered species can be used to inform management actions. In vagile species with high gene flow or recently established populations, such characterizations can be difficult to undertake using traditional genetic markers, and genetic stock identification (GSI) may be confounded by allele-sharing between populations. Loggerhead sea turtles ( Caretta caretta ) in the southeastern United States comprise seven management units (MUs) based on female philopatry inferred via mitochondrial DNA sequences, yet nuclear microsatellite data do not reflect divergence. Further, loci for accurate GSI are not currently known. To address this, we generated genome-wide single nucleotide polymorphism (SNP) data from 146 females nesting at individual sites representative of each southeastern United States MU. We found weak (F ST =0.001–0.003) but significant divergence among all MUs, with more notable divergence between the Gulf Coast and Atlantic Ocean MUs, and amongst the Atlantic Ocean MUs. We then used an iterative leave-one-out approach to identify candidate loci for GSI. This approach identified loci that could assign individuals to natal ocean basins (i.e., to the Gulf Coast or to the Atlantic Ocean), and to individual MUs within the Atlantic Ocean, with high (≥90%) success and accuracy. Analyses of genome-wide SNPs refined our understanding of the magnitude and scale of population connectivity in loggerhead turtles in the southeastern United States, and provided a foundation for the development of SNP panels for accurate, fine-scale GSI in sea turtles.

Associations of self-reported sleep quality and duration with dietary eating behaviours: a cross-sectional study of 27,263 UK adults - Scott A. Willis; Arwa Alruwaili; Iuliana Hartescu; Kevin Deighton; Christopher Goodwin; Joseph Henson; Alice E. Thackray; David J. Stensel; James A. King (Appetite, 2026)

Rapid deglacial retreat of a regional scale ice stream and late Holocene readvance in Vincennes Bay, east Antarctica - Marcello G. Blaxell; David Small; David Fink; Réka-H. Fülöp; Alexandru T. Codilean; Alexandra Post; Klaus Wilcken; Toshiyuki Fujioka; Sonja Berg; Ian Goodwin; Steven Phipps; Matthew R. Jeromson; et al. (Quaternary Science Reviews, 2026)

Psilocybin therapy for treatment resistant depression: prediction of clinical outcome by natural language processing - Robert F. Dougherty; Patrick Clarke; Merve Atli; Joanna Kuc; Danielle Schlosser; Boadie W. Dunlop; David J. Hellerstein; Scott T. Aaronson; Sidney Zisook; Allan H. Young; Robin Carhart-Harris; Guy M. Goodwin; et al. (Psychopharmacology, 2025)
Rationale Therapeutic administration of psychedelics has shown significant potential in historical accounts and recent clinical trials in the treatment of depression and other mood disorders. A recent randomized double-blind phase-IIb study demonstrated the safety and efficacy of COMP360, COMPASS Pathways’ proprietary synthetic formulation of psilocybin, in participants with treatment-resistant depression. Objective While the phase-IIb results are promising, the treatment works for a portion of the population and early prediction of outcome is a key objective as it would allow early identification of those likely to require alternative treatment. Methods Transcripts were made from audio recordings of the psychological support session between participant and therapist 1 day post COMP360 administration. A zero-shot machine learning classifier based on the BART large language model was used to compute two-dimensional sentiment (valence and arousal) for the participant and therapist from the transcript. These scores, combined with the Emotional Breakthrough Index (EBI) and treatment arm were used to predict treatment outcome as measured by MADRS scores. (Code and data are available at https://github.com/compasspathways/Sentiment2D .) Results Two multinomial logistic regression models were fit to predict responder status at week 3 and through week 12. Cross-validation of these models resulted in 85% and 88% accuracy and AUC values of 88% and 85%. Conclusions A machine learning algorithm using NLP and EBI accurately predicts long-term patient response, allowing rapid prognostication of personalized response to psilocybin treatment and insight into therapeutic model optimization. Further research is required to understand if language data from earlier stages in the therapeutic process hold similar predictive power.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

Mytilus galloprovincialis shell growth – Insights from shell geochemistry - Melita Peharda; Bernd R. Schöne; Krešimir Markulin; Hana Uvanović; Kentaro Tanaka; Kotaro Shirai; David Goodwin; Hrvoje Mihanović (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Reconstructed seasonality during the Mid Piacenzian Warm Interval and early Pleistocene cooling as recorded by growth temperatures from Mercenaria shells - Garrett F.N. Braniecki; Donna Surge; Ethan G. Hyland; David H. Goodwin (Quaternary Science Reviews, 2024)

Satellite tracking reveals use of Biscayne National Park by sea turtles tagged in multiple locations - Kristen M. Hart; Allison M. Benscoter; Haley M. Turner; Michael S. Cherkiss; Andrew G. Crowder; Jacquelyn C. Guzy; David C. Roche; Chris R. Sasso; Glenn D. Goodwin; Derek A. Burkholder (Regional Studies in Marine Science, 2023)

Quantitative evaluation of released nanomaterials from carbon nanotube epoxy nanocomposites during environmental exposure and mechanical treatment - Yue Zhao; David G. Goodwin; Lipiin Sung; Girish Ramakrishnan; Qiyuan Wu; Jiajie Cen; Elijah J. Petersen; Alexander Orlov (NanoImpact, 2023)

The spontaneous mouse mutant low set ears (Lse) is caused by tandem duplication of Fgf3 and Fgf4 - Alana Luzzio; Sarah Edie; Kristina Palmer; L. Brianna Caddle; Rachel Urban; Leslie O. Goodwin; Ian C. Welsh; Laura G. Reinholdt; David E. Bergstrom; Timothy C. Cox; Leah Rae Donahue; Stephen A. Murray (Mammalian Genome, 2023)

FDA and industry collaboration: Identifying opportunities to further reduce reliance on nonhuman primates for nonclinical safety evaluations - David Ackley; Joanne Birkebak; Jorg Blumel; Todd Bourcier; Christina de Zafra; Andrew Goodwin; Wendy Halpern; Danuta Herzyk; Sven Kronenberg; Robert Mauthe; Jacintha Shenton; Dana Shuey; et al. (Regulatory Toxicology and Pharmacology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying risks avoided by limiting global warming to 1.5 or 2 °C above pre-industrial levels - Rachel Warren; Oliver Andrews; Sally Brown; Felipe J. Colón-González; Nicole Forstenhäusler; David E. H. J. Gernaat; P. Goodwin; Ian Harris; Yi He; Chris Hope; Desmond Manful; Timothy J. Osborn; et al. (Climatic Change, 2022)
The Paris Agreement aims to constrain global warming to ‘well below 2 °C’ and to ‘pursue efforts’ to limit it to 1.5 °C above pre-industrial levels. We quantify global and regional risk-related metrics associated with these levels of warming that capture climate change–related changes in exposure to water scarcity and heat stress, vector-borne disease, coastal and fluvial flooding and projected impacts on agriculture and the economy, allowing for uncertainties in regional climate projection. Risk-related metrics associated with 2 °C warming, depending on sector, are reduced by 10–44% globally if warming is further reduced to 1.5 °C. Comparing with a baseline in which warming of 3.66 °C occurs by 2100, constraining warming to 1.5 °C reduces these risk indicators globally by 32–85%, and constraining warming to 2 °C reduces them by 26–74%. In percentage terms, avoided risk is highest for fluvial flooding, drought, and heat stress, but in absolute terms risk reduction is greatest for drought. Although water stress decreases in some regions, it is often accompanied by additional exposure to flooding. The magnitude of the percentage of damage avoided is similar to that calculated for avoided global economic risk associated with these same climate change scenarios. We also identify West Africa, India and North America as hotspots of climate change risk in the future.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

How long does it take to discover a species? - Zoë A. Goodwin; Pablo Muñoz-Rodríguez; David J. Harris; Tom Wells; John R. I. Wood; Denis Filer; Robert W. Scotland (Systematics and Biodiversity, 2020)

Long-term wear effects on nanosilver release from commercially available food contact materials - Susana Addo Ntim; David G. Goodwin; Lipiin Sung; Treye A. Thomas; Gregory O. Noonan (Food Additives & Contaminants: Part A, 2019)

Effects of consumer use practices on nanosilver release from commercially available food contact materials - Susana Addo Ntim; Samuel Norris; David G. Goodwin; Jens Breffke; Keana Scott; Lipiin Sung; Treye A. Thomas; Gregory O. Noonan (Food Additives & Contaminants: Part A, 2018)

Paleoclimate Reconstruction from Oxygen Isotopes in a Coral Skeleton from East Africa: A Data-Enhanced Learning Experience - David Gillikin; Anouk Verheyden; David Goodwin (Oceanography, 2017)

Interannual modulation of subtropical Atlantic boreal summer dust variability by ENSO - Michael J. DeFlorio; Ian D. Goodwin; Daniel R. Cayan; Arthur J. Miller; Steven J. Ghan; David W. Pierce; Lynn M. Russell; Balwinder Singh (Climate Dynamics, 2016)

Multiphyletic origins of methylotrophy in A lphaproteobacteria , exemplified by comparative genomics of L ake W ashington isolates - David A. C. Beck; Tami L. McTaggart; Usanisa Setboonsarng; Alexey Vorobev; Lynne Goodwin; Nicole Shapiro; Tanja Woyke; Marina G. Kalyuzhnaya; Mary E. Lidstrom; Ludmila Chistoserdova (Environmental Microbiology, 2015)
Summary We sequenced the genomes of 19 methylotrophic isolates from L ake W ashington, which belong to nine genera within eight families of the A lphaproteobacteria , two of the families being the newly proposed families. Comparative genomic analysis with a focus on methylotrophy metabolism classifies these strains into heterotrophic and obligately or facultatively autotrophic methylotrophs. The most persistent metabolic modules enabling methylotrophy within this group are the N ‐methylglutamate pathway, the two types of methanol dehydrogenase ( MxaFI and XoxF ), the tetrahydromethanopterin pathway for formaldehyde oxidation, the serine cycle and the ethylmalonyl‐ CoA pathway. At the same time, a great potential for metabolic flexibility within this group is uncovered, with different combinations of these modules present. Phylogenetic analysis of key methylotrophy functions reveals that the serine cycle must have evolved independently in at least four lineages of A lphaproteobacteria and that all methylotrophy modules seem to be prone to lateral transfers as well as deletions.

Relating Turbulence and Fish Habitat: A New Approach for Management and Research - David L. Smith; R. Andrew Goodwin; John M. Nestler (Reviews in Fisheries Science & Aquaculture, 2014)

Species-Specific Effects of Herbivory on the Oviposition Behavior of the Moth Manduca sexta - Carolina E. Reisenman; Jeffrey A. Riffell; Kristin Duffy; Adrien Pesque; David Mikles; Brenna Goodwin (Journal of Chemical Ecology, 2013)

On the long-term context of the 1997–2009 ‘Big Dry’ in South-Eastern Australia: insights from a 206-year multi-proxy rainfall reconstruction - Joëlle Gergis; Ailie Jane Eyre Gallant; Karl Braganza; David John Karoly; Kathryn Allen; Louise Cullen; Rosanne D’Arrigo; Ian Goodwin; Pauline Grierson; Shayne McGregor (Climatic Change, 2012)

Serum insulin-like growth factors and mortality in localised and advanced clinically detected prostate cancer - Mari-Anne Rowlands; Jeff M. P. Holly; Freddie Hamdy; Joshua Phillips; Louise Goodwin; Gemma Marsden; David Gunnell; Jenny Donovan; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2012)

Minimizing Variability of Cascade Impaction Measurements in Inhalers and Nebulizers - Matthew Bonam; David Christopher; David Cipolla; Brent Donovan; David Goodwin; Susan Holmes; Svetlana Lyapustina; Jolyon Mitchell; Steve Nichols; Gunilla Pettersson; Chris Quale; Nagaraja Rao; et al. (AAPS PharmSciTech, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of tree size on water use of peach (Prunus persica L. Batsch) - Ian Goodwin; Desmond M. Whitfield; David J. Connor (Irrigation Science, 2006)

Reliability of leg muscle electromyography in vertical jumping - Peter C. Goodwin; Kobus Koorts; Richard Mack; Shunfu Mai; Matthew C. Morrissey; David M. Hooper (European Journal of Applied Physiology, 1999)

Changes in gravity inhibit lymphocyte locomotion through type I collagen - Neal R. Pellis; Thomas J. Goodwin; Diana Risin; Bradley W. McIntyre; Roland P. Pizzini; David Cooper; Tacey L. Baker; Glenn F. Spaulding (In Vitro Cellular & Developmental Biology - Animal, 1997)

Nephrotic syndrome associated with N-hydroxyureas, inhibitors of 5-lipoxygenase - Nicholas G. Read; Paul J. Astbury; Gareth O. Evans; David A. Goodwin; Ann Rowlands (Archives of Toxicology, 1995)

The carotenoids of Flavobacterium strain R1560 - George Britton; David J. Brown; Trevor W. Goodwin; Franz J. Leuenberger; Arno J. Schocher (Archives of Microbiology, 1977)

Sectional notes - Frank E. Garrett; David N. Wright; Cecil W. Frutchey; W. B. Ward; Allen Purdy; John C. Campbell; H. J. Evans; C. A. Henderson; W. C. Barnes; John Noonan; Edwin W. Cake; Claude R. Kemper; et al. (American Journal of Potato Research, 1948)